Fabrication, characterization and simulation of Ω-gate twin poly-Si FinFET nonvolatile memory - Yeh, Mu-Shih (Springer, 2013)
This study proposed the twin poly-Si fin field-effect transistor (FinFET) nonvolatile memory with a structure that is composed of Ω-gate nanowires (NWs). Experimental results show that the NW device has superior memory characteristics because its Ω-gate structure provides a large memory window and high program/erase efficiency. With respect to endurance and retention, the memory window can be maintained at 3.5 V after 10(4) program and erase cycles, and after 10 years, the charge is 47.7% of its initial value. This investigation explores its feasibility in the future active matrix liquid crystal display system-on-panel and three-dimensional stacked flash memory applications.